The impact of government incentives on financial viability of selected aquaculture species in Malaysia - Ramzani, Sara Ravan; Ismail, Mohd Mansor; Kamarulzaman, Nitty Hirawaty; Mohamed, Zainal Abidin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Aquaculture businesses in Malaysia require careful and comprehensive financial analysis to be successful. Comprehensive financial analysis has three key components, namely financial position, profitability and liquidity/cash flow. This research focuses on using pro forma income statements to analyze financial positions and to evaluate the effect of government incentives on sustainability of Malaysian aquaculture farms. This paper is divided into two sections; the first section discusses and provides the finding and comparability of the financial analysis on freshwater and brackish water producers. In the first section, the discussion was based on financial viability criteria, namely net present value (NPV), internal rate of return (IRR) and benefit cost ratio (BCR)) for base study. The evaluation process was carried out using four different phases; base study and government incentives simulations, Pioneer Status (PS), Investment Tax Allowance (ITA), and Accelerated Capital Allowance (ACA) for effectiveness of government incentives and roles in increase of profitability and production. The results showed that in all brackish water farms, NPV after the ACA incentive showed a higher and positive value comparable to individual PS and ITA. The effect of Government Incentive on Penaeus vannamei and Grouper showed that IRR and NPV on ACA (based on PS) is 2% and 9%, respectively higher than ACA (based on ITA). Meanwhile, in Barramundi farming ACA (based on ITA) was 8% higher than ACA (based on PS). The results on freshwater showed that ACA (based on ITA) on Tilapia and Catfish was 8% and 6% higher than ACA (based on PS). This paper concludes that the aquaculture operators should choose to accept PS with ACA on Penaeus vannamei and Grouper and choose ACA based on ITA on Barramundi, Tilapia and Catfish in order to maximize private profitability.